2013
DOI: 10.1007/s00244-013-9924-2
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Concentrations of Parabens in Chinese Young Adults: Implications for Human Exposure

Abstract: Parabens are widely used as preservatives in foods, cosmetics, and pharmaceuticals. However, recent studies have indicated that high and systemic exposure to parabens can be harmful to human health. Although a few studies have reported urinary paraben levels in western countries, studies on paraben exposure in the Chinese population are limited. China is currently a major producer of parabens in the world. In this study, 109 urine samples collected from Chinese young adults (approximately 20 years old) were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
30
6
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(47 citation statements)
references
References 33 publications
9
30
6
2
Order By: Relevance
“…In the present study, the maximum estimated daily intake (EDI) for total parabens from swimming pool water, based on body weights of 70 and 15 kg for adults and children, were 5.39 and 15.9 ng kg −1 body weight per day, respectively, indicating that children are more sensitive than adults to the potential health risks. Previous studies have reported that the EDI for the total parabens for adults and children are 74.4 and 40.8 μg kg −1 body weight per day, respectively (Asimakopoulos et al 2014;Ma et al 2013). These values were several orders of magnitude higher than the maximum EDI for the total parabens from swimming pool water, suggesting that human exposure to parabens from swimming pools is negligible.…”
Section: Human Exposure Assessmentmentioning
confidence: 84%
“…In the present study, the maximum estimated daily intake (EDI) for total parabens from swimming pool water, based on body weights of 70 and 15 kg for adults and children, were 5.39 and 15.9 ng kg −1 body weight per day, respectively, indicating that children are more sensitive than adults to the potential health risks. Previous studies have reported that the EDI for the total parabens for adults and children are 74.4 and 40.8 μg kg −1 body weight per day, respectively (Asimakopoulos et al 2014;Ma et al 2013). These values were several orders of magnitude higher than the maximum EDI for the total parabens from swimming pool water, suggesting that human exposure to parabens from swimming pools is negligible.…”
Section: Human Exposure Assessmentmentioning
confidence: 84%
“…Moreover, synergistic effects between phthalates and pesticides have been reported (Christiansen et al, 2009) and are not included in the HI cumulative model. In this risk assessment, parabens and BP3 were not included because, until now, there is too much lack of knowledge and too many uncertainties on the toxicokinetics of these compounds (Ma et al, 2013;Søeborg et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Phthalates, parabens and BP3 are three chemical classes of nonpersistent endocrine-disrupting pollutants eliminated from the human body within a day (Anderson et al, 2001;Ma et al, 2013;Gonzalez et al, 2006). However, since human exposure occurs daily, the question of the temporal representativeness of the urinary biomarker measurements could be raised (Dewalque et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parabens have been quantified in the vast majority of human urine samples in biomonitoring studies from different parts of the world , Frederiksen et al 2011b, Ma et al 2013. Humans are exposed to parabens mainly via personal care products and cosmetics, as reviewed e.g.…”
Section: Parabensmentioning
confidence: 99%